Differences in Before and After Temephos Intervention in Bengkulu City: Larvae Free Rate of Aedes spp. - Gunasari, Lala Foresta Valentine; Destilyana, Rizqita; Massardi, Nikki Aldi; Triana, Dessy (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
One of the strategies to reduce dengue transmission is to control the population of vectors, such as larval eradication. The use of temephos larvicide (Abate®) is the most widely carried out in the community. An indicator of the success of the larval eradication program is the Larvae Free Rate (LFR) assessment. This study aimed to determine the difference between LFR of Aedes spp. before and after temephos intervention in Bengkulu City. This study is experimental research with one group pre-test and post-test design. The population of this study was all houses in Bengkulu City with a total sample of 670 houses. Sampling was carried out using cluster random sampling techniques in 67 urban villages in Bengkulu City. This research was carried out by conducting a survey of larvae before and after temephos intervention in containers. Sixty-seven urban-villages, in 44 (65,67%) urban-villages was found an increase of LFR after temephos intervention. The average LFR before temephos intervention was 67.61%, while after temephos intervention increased to 82.98%, there was a significant difference between LFR of Aedes spp. before and after temephos intervention in Bengkulu City (p=0.001). Temephos intervention is effective to increase LFR of Aedes spp. in Bengkulu City.